Monday

April 21, 2014

April 21, 2014

Posted by **barb** on Thursday, August 5, 2010 at 4:19pm.

- math -
**Ms. Sue**, Thursday, August 5, 2010 at 4:31pm6-3(3x-1)=-18

6 - 9x + 3 = -18

-9x = -18 + (-9)

-9x = -27

x = 3

**Related Questions**

math,algebra,help - Directions are simplify by combining like terms. x radiacal ...

Math - AlgebrAic factorization 1)6(2a-3)(a+7)+18(2a-3)(3a+2) 2) (3x-4)(5x+1)-(...

algebra1/McDougal Littell - I need to know how to work this problem and show my ...

Pre-calculus - fraction 1) 5/12+7/18-5/6 2) 3x/x-1-1/x=_____/x^2-1x 3) x+1/x^2-...

math,correction - Problem #1 subtract. Express your answer in simplest form (3x...

math - What is 3(x +4) - 2(3x - 3) simplified a) -3x + 18 b) -3x + 12 c) -9x + ...

ALGebra - Can you check 2x + 3 (x-2) -3 (x-6) I got 2x+3x-6 -3x+18 2x+3x-3x= 2x...

College Math - (2x-1/x+3)+(x+4/x-6)+(3x-1/x^2-3x-18)

math - 2x^3+4x^2-3x^2-6x when x=3 I did2(3)^3+4(3)^2-3(3)^2-6(3) 2(27)+4(9)-3(9...

math - 3x+y+2z=1 x+2y-z=-8 3x-y-3z=18 after I isolate x what is the 2nd equation